2020
DOI: 10.17309/tmfv.2020.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Research Program: Modeling of Motor Abilities Development and Teaching of Schoolchildren

Abstract: The purpose of this study was to find methodological approaches to the development of a research program in modeling the process of teaching physical exercises, motor abilities development and pedagogical control in schoolchildren’s physical education. Materials and methods. The total number of schoolchildren involved in the experiment was: 6-10 years old – 465 (240 boys and 225 girls); 11-13 years old – 430 schoolchildren (205 boys and 225 girls); 14-16 years old – 221 schoolchildren (122 boys and 99 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 17 publications
8
46
0
3
Order By: Relevance
“…Normalization of physical loads in physical education classes is one of the factors that ensure the effectiveness of schoolchildren's physical education (Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018;Veremeenko, Khudolii, & Ivashchenko, 2019;Ivashchenko, 2020). Washabaugh, Augenstein, and Krishnan (2020), Benzing, and Schmidt (2019) emphasize the use of dosed efforts in both physical education and sports training.…”
Section: Introductionmentioning
confidence: 99%
“…Normalization of physical loads in physical education classes is one of the factors that ensure the effectiveness of schoolchildren's physical education (Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018;Veremeenko, Khudolii, & Ivashchenko, 2019;Ivashchenko, 2020). Washabaugh, Augenstein, and Krishnan (2020), Benzing, and Schmidt (2019) emphasize the use of dosed efforts in both physical education and sports training.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the level of coordination abilities development determines the success in developing motor skills (Khudolii, 2019;Marchenko & Dykhanova, 2019;Ivashchenko, 2020), but the results of testing coordination abilities showed that the girls and boys did not statistically significantly differ by these indicators (Table 1) and had a statistically significant difference in the level of proficiency in acrobatic exercises. For the girls, the proposed acrobatic exercises are difficult to perform.…”
Section: Discussionmentioning
confidence: 96%
“…To identify the patterns of motor function development, modern research uses methods of multivariate statistics such as factor and discriminant analysis (Brusseau & Burns, 2018;Hohmann, Siener, & He, 2018;Ivashchenko, 2020). Discriminant analysis allows to obtain both a regression equation to classify schoolchildren by their motor fitness level, and to Ivashchenko, O., Nosko, Yu., Bartik, P., & Makanin, O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focus on the organization of pedagogical control in physical education classes (Ivashchenko, 2020;Koryahin, Blavt, & Ponomaryov, 2019), means and methods of influence (Chen, Dai, & Gao, 2017;Ivashchenko, Khudolii, Iermakov, Lochbaum, Cieslicka, Zukow, Nosko, & Yermakova, 2016;Skead & Rogers, 2016), and also on the use of pedagogical techniques of physical education with different nosologies in the educational process (Adyrkhaev, 2016;Bondar, 2000;Orikhovska, Andrieieva, Kashuba, Lazarieva, Lytvynenko, Kirichenko, Arefyiev, & Khrypko, 2020).…”
Section: Introductionmentioning
confidence: 99%